External validation of the REMEMBER score - Peivandi, Armin Darius; Welp, Henryk; Kintrup, Sebastian; Wagner, Nana Maria; Dell’Aquila, Angelo Maria (Frontiers in Cardiovascular Medicine, 2023)
Background: Use of Venoarterial extracorporal membrane oxygenation (VA-ECMO) after coronary artery bypass grafting (CABG) is associated with high in-hospital mortality rates. The pRedicting mortality in patients undergoing veno-arterial Extracorporeal MEMBrane oxygenation after coronary artEry bypass gRafting (REMEMBER) score has been created to predict in-hospital mortality in this sub-group of patients. The aim of this study was to externally validate the REMEMBER score. Methods: All CABG patients receiving VA-ECMO during or after the operation at our center from 01/2012 to 12/2021 were included in the analysis. Discrimination was assessed using concordance statistics, visualized by ROC curve analysis. Calibration-in-the-large and Calibration slope were tested separately. Results: 107 patients (male: n=78, 72.9%) were included in this study. In-hospital mortality in our cohort was 45.8% as compared to 55% in the original study. Median predicted mortality by REMEMBER score was 52 % (76.9 - 36%). However, REMEMBER score showed low discriminative ability (AUC: 0.623 (p=0.0244; 95% CI= 0.524 – 0.715)) and inaccurate calibration (intercept=0.25074; p=0.0195; slope=0.39504; p=0.0303), indicating poor performance. Conclusions: The REMEMBER score did not predict in-hospital mortality and was therefore not applicable in our cohort of patients. Additional external validation studies in a multi-center setting are therefore advisable.